USP21 prevents the generation of T-helper-1-like Treg cells - Li, Y; Lu, Y; Wang, S; Han, Z; Zhu, F; Ni, Y; Liang, R; Zhang, Y; Leng, Q; Wei, G; Shi, G; Zhu, R; et al. (Springer Nature, 2016)
FOXP3+ Regulatory T (Treg) cells play a key role in the maintenance of immune homeostasis and tolerance. Disruption of Foxp3 expression results in the generation of instable Treg cells and acquisition of effector T-cell-like function. Here we report that the E3 deubiquitinase USP21 prevents the depletion of FOXP3 at the protein level and restricts the generation of T-helper-1-like Treg cells. Mice depleted of Usp21 specifically in Treg cells display immune disorders characterized by spontaneous T-cell activation and excessive T-helper type 1 (Th1) skewing of Treg cells into Th1-like Treg cells. USP21 stabilizes FOXP3 protein by mediating its deubiquitination and maintains the expression of Treg signature genes. Our results demonstrate how USP21 prevents FOXP3 protein depletion and controls Treg lineage stability in vivo.